Evolution of Fe-Ti-V oxides from the main magnetite layer, Upper Zone, Bushveld Complex, South Africa: a comparison across the Western, Northern and Eastern Lobes - Iorga-Pavel, Adina (Rhodes University, Faculty of Science, Department of Geology, 2017)
The Main Magnetite Layer (MML) from the Northern, Eastern and Western lobes of the Bushveld Complex shows significant differences in textures and in mineral chemistry. The MML in the Eastern and Western lobes is massive, with rare, small and altered pyroxene inclusions. By contrast, the MML in the Northern Lobe is more heterogeneous, and it is made of anastomosed and sometimes imbricated, thin layers of magnetitite, magnetite-rich and silicate-rich rocks, where the inclusions in Ti-magnetite are more numerous and consist of mainly altered subhedral and anhedral plagioclase. The comparison of the maximum values of the oxides shows that the MML in the Northern Lobe has the highest content of V2O3 (1.97 wt%), TiO2 (22.49 wt%) and MgO (2.92 wt%), while the MML in the Eastern Lobe has the highest content of Cr2O3 (2.92 wt%) and Al2O3 (9.80 wt%), but lowest V2O3 (0.52 wt%). The lower TiO2 content and higher V2O3 content in the MML of the Northern and Western Lobes suggest lower oxidising conditions during the crystallization of oxides. The MML in all three studied lobes consists of two layers of magnetitite, suggesting that MML was formed by two separate magma influxes, probably on a diverse and complex type of magma chamber floor. The high TiO2 content in magnetite, together with the negative correlation between TiO2 and V2O3 suggest that the maximum V content should represent a "less evolved" and less oxidized melt. In this respect, higher concentrations V2O3 in magnetite can be expected in magnetitite layers with lower TiO2. It can be inferred that the Ti-magetite in the MML from the Eastern Lobe was formed from a more evolved (TiO2 and FeO enriched) and more oxidized (lower V2O3) melt, compared with the MML from the Northern and Western lobes. These findings can be used to illustrate: a) that high fO2 can be responsible for the relatively low V content in magnetite from Fe-Ti oxide ores and b) the vanadium in magnetite decreases significantly in more evolved cumulates, due to a decreasing fO2 with differentiation. Compositional profiles of Ti- magnetite along the stratigraphic height of the MML in the Eastern Lobe (composed of two layers, separated in the outcrop by a parting plane) depicts a cryptic variation with depth in each of the two layers, where each layer can be divided into four sublayers, labelled upwards as A, B, C (with C1, C2, C3 and C4) and D based on Cr, Mg, Ti, Al and V variation. Small scale reversals of the mentioned elements and the repetition of A, B, C and D sub-layers in each layer suggest that MML formed from two successive influxes of magma (indicated by relatively elevated values of MgO), which evolved by crystallization and cooling in a similar manner, to produce the A to D variation. Based on these observations and theoretical considerations, this study dismisses several models for the genesis of the MML: the immiscibility, the increased oxygen fugacity, the relative increase of H2O content of the melt, pressure variation within the magma chamber, magma mixing, and crustal rock contamination. The model proposed here for MML genesis involves the crystallization of both Ti-magnetite and ilmenite from a Fe-Ti-Ca-Al-rich melt (ferro-diorite) along its line of descent, and gravitational settling of oxides in a dynamic regime. The factor which triggered the crystallization of magnetite is a critical saturation of melt in magnetite (attaining saturation of magnetite and ilmenite in the melt after some silicates crystallized). The difference between the nature of silicate inclusions in magnetite and the nature of the magnetite floor, suggest that the Fe-rich magma was not in equilibrium with the cumulates from the present floor, but rather it was emplaced laterally on long distances, the melt being disrupted from its own cumulates. The absence of correlation between the Cr2O3 in magnetite and co-existing ilmenite can indicate than no in-situ fractional crystallization took place at the moment of magnetite accumulation, but rather that magnetite and ilmenite gravitationally accumulated and the grains mechanically mixed from a flowing magma. The model presented herein proposes a five stage model of MML formation: Stage 1 is represented by the intrusion of a Fe-T-Ca-Al-rich magma which expands laterally within a flat and thin magma chamber. Oxides start to crystallize within a dynamic regime of the magma. Stage 2 is given by the accumulation of oxides at the bottom of the new floor. Some plagioclase starts to crystallize (e.g. subhedral plagioclase in the MML of the Northern Lobe). Stage 3 is a short living static regime, where both plagioclase and magnetite crystallized, without fractionation, forming the thin magnetite-anorthosite layer separating the MML into two layers. Stage 4 is represented by a new influx of Fe-Ti-Ca-Al-rich magma which is emplaced above the magnetite-bearing anorthosite, flushing out the liquid which was in equilibrium with the anorthosite. The oxides started crystallizing in a dynamic regime, as in Stage 1. In stage 5, the accumulation of oxides produced the upper layer of the MML. Our interpretation is that the flow of the magma was more dynamic (probably more turbulent on long distances) in the MML of the Northern Lobe, compared to the MML in the Western and Eastern lobes, producing highly heterogeneous and imbricated thin layers of magnetitite and silicates. The presence of olivine corona around orthopyroxene suggests the incongruent melting of orthopyroxene, which points out towards a local re-heating of existing silicate layers, this being a strong argument for multiple injections in generation of MML. Massive crystallization of oxides produced the sulphur saturation of the magma and caused the precipitation of the igneous sulphides, which nucleated on the existing oxides. Later hydrothermal fluids (and/or late magmatic volatiles?) percolated the MML, producing chloritization of the included silicates, remobilization of igneous sulphides and precipitation of hydrothermal sulphides.
Keywords: Magnetite -- South Africa -- Bushveld Complex; Mineralogy -- South Africa -- Bushveld Complex; Oxides